2019
DOI: 10.21203/rs.2.10861/v3
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Prestroke statins use reduces oxidized low density lipoprotein levels and improves clinical outcomes in patients with atrial fibrillation related acute ischemic stroke

Abstract: Background: Atrial fibrillation (AF) is a common cause of cerebral infarction, which could lead to endothelial dysfunction, increased reactive oxygen species (ROS) and oxidized low density lipoprotein (Ox-LDL).AF is associated with higher mortality and more severe neurologic disability. Statins may exert neuroprotective effects that are independent of LDL-C lowering. The purpose of our study was to investigate whether prestroke statins use could reduce plasma Ox-LDL levels and improve clinical outcomes in pati… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
1
0
0
Order By: Relevance
“…A cohort study showed that prestroke statin use among patients with AF-related ischemic stroke was associated with a significantly reduction of disease progression and 30 days mortality [37,38]. Consistent with previous study, our data suggested that prestroke statin use improved disease prognosis in AF-AIS patients [39].…”
Section: On Admissionsupporting
confidence: 91%
“…A cohort study showed that prestroke statin use among patients with AF-related ischemic stroke was associated with a significantly reduction of disease progression and 30 days mortality [37,38]. Consistent with previous study, our data suggested that prestroke statin use improved disease prognosis in AF-AIS patients [39].…”
Section: On Admissionsupporting
confidence: 91%